Vulnerability of homeless people in Tehran, Iran, to HIV, tuberculosis and viral hepatitis. - Fahimeh Bagheri Amiri (Public Library of Science (PLoS), 2014)
Background Homeless people are at risk of contracting communicable infectious diseases, as they indulge in risky behaviours and lifestyle. This study was conducted to determine the prevalence of the aforementioned infections and related risk behaviours among homeless people in Tehran. Methods In this study a convenience sample of 593 homeless individuals was studied. The ELISA method was used for the detection of HIV, HCV and HBV. Clinical symptoms, sputum cultures, acid fast bacilli smears, and chest X-rays were used to identify active pulmonary tuberculosis, and the Interferon Gamma Release Assay (IGRA) test was used to identify latent tuberculosis. Results The prevalence of HIV, HBV, HCV and latent tuberculosis was 3.4%, 2.6%, 23.3% and 46.7%, respectively. Active pulmonary tuberculosis was found in 7 persons (1.2%). Injection drug use was an independent risk factor for HIV, HCV and HBV infections. Older people had a higher proportion of Mycobacterium tuberculosis infection (OR: 2.6, 95%CI: 1.9, 3.7) and HCV positivity (OR: 1.7, 95% CI: 1.1, 2.5). Conclusion Our findings highlighted that much more attention needs to be paid to the health of homeless people.